Impact of country of origin and national identity on air travel purchase decisions for prospective buyers: The case of American travelers - Talha Harcar; Ersem Karadag (Journal of Global Business Insights, 2022)
This study focuses on how the concept of country of origin (COO) and national loyalty affect purchasing decisions of prospective travelers when purchasing airline tickets. The objectives of this study are to understand: (a) the relationship between demographic structures of travelers and their national loyalty status, (b) the relationship between national loyalty and national airline perceptions, (c) the construction and analysis of the measurement of national airline preference scale, and (d) testing the relationship between national loyalty, national airline perception, and preferences of foreign airlines. Data collected from 136 people residing and employed in three districts of Pennsylvania. The study findings denote that the national loyalty status of travelers affects the purchasing behaviors of air travelers. Prospective travelers do not prefer foreign airline service providers, thinking that they may damage the national airline companies and national economy. The effects of national loyalty include overrating the service quality and merit of national airlines and underrating the merits of foreign airline services. The findings of this research propose that foreign airline companies should convince international travelers that preferring their services over other airlines would not result in a disadvantage of national airlines or deteriorate economic conditions in their home countries.